Modal verbs expressing deontic necessity in administrative style - Filipová, Michaela (Univerzita Pardubice, 2009)
This bachelor thesis deals with modal verbs expressing deontic necessity in administrative style. The theoretical part defines the term "modality" and states two main kinds of modality. Furthermore, it concentrates on characteristic features and functions of individual modal verbs expressing deontic necessity. In the practical part, the theory is applied to the documents of administrative style in order to state the frequency of occurrence of selected modals as well as to prove or disprove the presumption stated.
Modální slovesa vyjadřující deontickou nutnost v administrativním stylu
Keywords: Modalita; deontická modalita; deontická nutnost; administrativní styl; Modality; deontic modality; deontic necessity; administrative style